The bridge to nowhere - McDonald, Megan (New York : Orchard Books, 1993)
Seventh grader Hallie is adjusting to friendship with an exciting older boy when her father, a bridge builder temporarily out of work, becomes an angry stranger in his own house.
"A Richard Jackson book"--Half-title.
Booklist.
Publisher's Weekly.
School Library Journal.
5.4
5.4
Keywords: Emotional problems -- Fiction; Fathers and daughters -- Fiction; Emotional problems -- Fiction; Father-daughter relationship -- Fiction